Differential regulation of gene expression by diacyglycerol-lactones and phorbol esters via selective activation of protein kinase c isozymes - Cooke, Mariana (2019)
Despite our extensive knowledge on the biology of protein kinase C (PKC) and its involvement in disease, limited success has been attained in the generation ofPKC isozyme-specific modulators acting via the C1 domain, the binding site forthe lipid second messenger diacylglycerol (DAG) and the phorbol ester tumorpromoters. Synthetic efforts had recently led to the identification of AJH-836, aDAG-lactone with preferential affinity for novel isozymes (nPKCs) relative toclassical PKCs (cPKCs). Here, we compared the ability of AJH-836 and aprototypical phorbol ester (phorbol 12-myristate 13-acetate, PMA) to inducechanges in gene expression in a lung cancer model. Gene profiling analysis using RNA-Seq revealed that PMA caused major changes in gene expression, whereasAJH-836 only induced a small subset of genes, thus providing a strong indication for a major involvement of cPKCs in their control of gene expression. MMP1, MMP9,and MMP10 were among the genes most prominently induced by PMA, an effectimpaired by RNAi silencing of PKCα, but not PKCδ or PKCε. Comprehensive genesignature analysis and bioinformatics efforts, including functional enrichmentand transcription factor binding site analyses of dysregulated genes, identified major differences in pathway activation and transcriptional networks between PMA and DAG-lactones. In addition to providing solid evidence for the differentialinvolvement of individual PKC isozymes in the control of gene expression, ourstudies emphasize the importance of generating targeted C1 domain ligands capableof differentially regulating PKC isozyme-specific function in cellular models.